LACTATIONAL AMENORRHEA AS A METHOD OF POSTPARTUM CONTRACEPTION - Rakhmonqulova Nargiza Gofurovna; Mukhitdinov Shokhrukh Shavkatovich (Galaxy International Interdisciplinary Research Journal, 2022)
The questions of the duration of lactational amenorrhea in 40 lactating women after physiological childbirth are considered.